Digital Formaldehyde Meter Performance Test to Detect Formaldehyde Content in Solid and Liquid Materials Using Electronic Nose Technology - Agung Heru Yatmo (Contributions of Central Research Institute for Agriculture, 2021)
Test results from the Food and Drug Supervisory Agency (BPOM) stated that out of 700 samples of food products taken from Java, 56% contained formaldehyde. The danger of formalin abuse can cause disease, both chronic and acute effects. The government, especially BPOM and the wider community, need a formalin detection test method to determine the formaldehyde content precisely, but currently there is no fast detector available at an affordable price. Testing of Solid Samples and Liquid Samples in Design to determine the performance of the tool in direct testing. The Digital Formaldehyde Meter test method uses a solid sample (the sample is cut into 3 cm as much as 5 grams) tested placed in a closed container with a volume of 30 ml and a liquid sample with a volume of 30 ml, then heated for 1 minute and the results will be displayed on the LCD. The test results showed that the average tool error for testing liquid samples was 2.78% while for solid samples it was 2%. Tests on several foods obtained from the market such as meatballs, sausages, and tofu have formalin levels that are safe for consumption, while marine fish are dangerous for consumption. In addition, it has also been confirmed that the "Digital Formaldehyde Meter" tool can be implemented to overcome problems in cases of formalin abuse by knowing the formaldehyde content quickly and accurately.